In Vitro and in Silico Analysis of Phytochemicals From Fallopia dentatoalata as Dual Functional Cholinesterase Inhibitors for the Treatment of Alzheimer’s Disease - Wu, Yichuang; Su, Xiangdong; Lu, Jielang; Wu, Meifang; Yang, Seo Young; Mai, Yang; Deng, Wenbin; Xue, Yongbo (Frontiers in Pharmacology, 2022)
Current studies have found that butyrylcholinesterase (BuChE) replaces the biological function of acetylcholinesterase (AChE) in the late stage of Alzheimer’s disease. Species in the genus of Fallopia, rich in polyphenols with diverse chemical structures and significant biological activities, are considered as an important resource for screening natural products to against AD. In this study, thirty-four compounds (1–34) were isolated from Fallopia dentatoalata (Fr. Schm.) Holub, and their inhibitory effects against AChE and BuChE were assessed. Compounds of the phenylpropanoid sucrose ester class emerged as the most promising members of the group, with 31–33 displaying moderate AChE inhibition (IC50 values ranging from 30.6 ± 4.7 to 56.0 ± 2.4 µM) and 30–34 showing potential inhibitory effects against BuChE (IC50 values ranging from 2.7 ± 1.7 to 17.1 ± 3.4 µM). Tacrine was used as a positive control (IC50: 126.7 ± 1.1 in AChE and 5.5 ± 1.7 nM in BuChE). Kinetic analysis highlighted compounds 31 and 32 as non-competitive inhibitors of AChE with Ki values of 30.0 and 34.4 µM, whilst 30–34 were revealed to competitively inhibit BuChE with Ki values ranging from 1.8 to 17.5 µM. Molecular binding studies demonstrated that 30–34 bound to the catalytic sites of BuChE with negative binding energies. The strong agreement between both in vitro and in silico studies highlights the phenylpropanoid sucrose esters 30–34 as promising candidates for use in future anti-cholinesterase therapeutics against Alzheimer’s disease.